Hipostaza, ateista i Sługa Jahwe, czyli trzy koncepcje samotności w filozofii Emmanuela Levinasa. - Jędraszewski, Marek (Filozofia Chrześcijańska, 2015)
Solitude is, to some measure, in the centre of Emmanuel Levinas’s philosophy. Indeed, in each of the three periods of his philosophical path, solitude adopts a different shape. In the first period, Levinas shows us hypostasis as the solitude of the monad, tragically enclosed within itself. In the second period he sketches before our eyes the image of solitude as a transcendental condition of the occurrence of encounter with the Other. Whereas in the third period, he asserts the solitude of the subject who is infinitely responsible for Others. Admittedly, the term “solitude” (la solitude) appears only in the first period of his philosophical quest. In the second period, he designates solitude by the terms “separation” (la séparation), while in the third period he calls it “selfness” (le Soi). Although Levinas uses those three distinct terms, which might suggest completely different realities, they converge precisely in what constitutes the substantial richness of the experience of solitude.